Treatment method of sugar alcohol phase change material
By freeze-thawing, water mixing and purification steps of the sugar alcohol phase change material, combined with the method of carrier gas inlet, the problem of supercooling of the sugar alcohol phase change material during cooling and low heat energy release efficiency is solved, and the efficient crystallization and stability of the material are improved.
Patent Information
- Application Number
- CN202311639154.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2025-06-03
AI Technical Summary
The melt viscosity of sugar alcohol phase change materials increases rapidly when they cool down, hindering the crystallization process, leading to supercooling and low heat energy release efficiency, limiting their large-scale use in the field of thermal energy storage.
The sugar alcohol phase change material is purified by freeze-thawing treatment, water mixing reaction, centrifugation of supernatant, concentration treatment, organic solvent precipitation, water dissolution, mixing organic amine and inorganic ammonium, running water dialysis, freeze-drying, etc., and combined with carrier gas to promote crystallization and reduce supercooling.
The crystallization speed of the sugar alcohol phase change material is significantly improved, the supercooling degree is reduced, the accuracy of the phase change peak position and the high latent heat value of the phase change are ensured, and stability is maintained during multiple endothermic-exothermic cycles.
Smart Images

Figure CN120082329A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of purification of phase change materials, and particularly relates to a method for treating sugar alcohol phase change materials. Background Art
[0002] Latent heat thermal energy storage technology uses a heat storage material to undergo a phase change under approximately constant temperature conditions, and realizes the rapid absorption, storage and release of energy through the heat exchange between the phase change system and the environment. It is one of the currently efficient and safe thermal energy storage technologies. A thermal energy storage unit using a medium-temperature phase change material as the core can store or release thermal energy through the phase change of the internal material. Sugar alcohol phase change materials are formed by reducing aldehyde or ketone groups on monosaccharide or polysaccharide molecules to hydroxyl groups. They are a type of polyhydroxy polyol, with advantages such as relatively high thermal grade, stable properties, non-toxic and non-corrosive, and have gradually become one of the mainstream application materials in medium-temperature phase change materials. However, when the sugar alcohol phase change material cools down, the melt viscosity will increase rapidly, hindering the crystallization process and causing vitrification transformation. At the same time, metastable and stable crystals are formed, resulting in a relatively serious supercooling phenomenon during its solidification stage. These disadvantages also lead to the delayed and inefficient release of its thermal energy, that is, reducing the utilization rate of thermal energy, and to a certain extent restricting its large-scale use in the field of thermal energy storage.
[0003] CN112815756A discloses a heat storage phase change heat exchanger and a method for promoting the crystallization of sugar alcohol phase change materials and reducing supercooling. At both ends of the heat exchanger body, an electrode is provided in the internal area of the liquid-phase sugar alcohol phase change heat storage material, and the upper and lower electrodes are respectively connected to an external impulse alternating power supply. Among them, the addition amount of stearate is 1% - 5% of the mass of the sugar alcohol. The stearate enables the sugar alcohol phase change material to be electrically conductive, and the stearate generates charged ions. Under the action of alternating current, the sugar alcohol phase change material can be disturbed to promote its crystallization and reduce supercooling. However, this method does not purify the sugar alcohol phase change material, and some sugar alcohol components are in a state of uneven chemical structure, affecting its enthalpy value and thermal stability.
[0004] CN112011312A discloses a phase change energy storage material and its preparation method. This phase change energy storage material is made from erythritol with a mass percentage of 70% - 95% and disodium succinate hexahydrate with a mass percentage of 5% - 30% as raw materials. The phase change temperature range of this phase change material is 70.2°C - 106.8°C, and the supercooling degree is as low as 2.4°C - 3.4°C, which better solves the supercooling problem of erythritol as a phase change material. However, disodium succinate hexahydrate, as one of the inorganic hydrated salts, is prone to phase separation and supercooling itself, so its restraint on the supercooling degree of erythritol is limited. Summary of the Invention
[0005] To overcome the deficiencies of the prior art, the present invention provides a method for treating sugar alcohol phase change materials. The sugar alcohol phase change materials obtained by the treatment method provided by the present invention have the advantages of fast crystallization rate, low supercooling degree, accurate phase change peak position, high phase change latent heat value, and good repeatability.
[0006] In the first aspect of the present invention, a method for treating sugar alcohol phase change materials is provided, including the following steps:
[0007] (1) After freeze-thawing, the sugar alcohol phase change material is mixed with water, reacted, centrifuged to obtain the supernatant, concentrated, then an organic solvent is added and allowed to stand. After obtaining the precipitate, it is dissolved in water, and then an organic amine and / or inorganic ammonium are added and mixed. The supernatant is taken, dialyzed against running water, and freeze-dried to obtain the purified sugar alcohol phase change material;
[0008] (2) The purified sugar alcohol phase change material obtained by freeze-drying in step (1) is heated and melted, and a carrier gas is introduced to obtain the treated sugar alcohol phase change material.
[0009] Further, in step (1), the sugar alcohol phase change material is selected from at least one of sugar alcohols with a phase change temperature in the range of 90°C to 180°C, such as at least one of xylitol, erythritol, and D-mannitol.
[0010] Further, in step (1), the freeze-thawing is at least three times or more, preferably 3 to 6 times. The freeze-thawing refers to the alternation between freezing and melting.
[0011] Further, in step (1), after the sugar alcohol phase change material is freeze-thawed, water is added, and the mass ratio of the sugar alcohol phase change material to water is 1:(0.6 to 2.5), preferably 1:(1 to 1.7).
[0012] Further, in step (1), the reaction is a heating dynamic reaction, the temperature is 35°C to 90°C, preferably 46°C to 65°C; and it is carried out under stirring, the stirring speed is 50 rpm to 600 rpm, preferably 200 rpm to 400 rpm, and the stirring time is 0.5 h to 8 h, preferably 3 h to 6 h.
[0013] Further, in step (1), the concentration treatment is under vacuum conditions. After the vacuum concentration treatment, the volume of the vacuum object is 8% to 45% of the original volume, preferably 15% to 33%.
[0014] Further, in step (1), the organic solvent is selected from one or more of acetonitrile, N,N-dimethylacetamide, and benzyl alcohol, preferably benzyl alcohol.
[0015] Further, in step (1), the standing treatment time is 6 h to 30 h, preferably 12 h to 20 h.
[0016] Further, in step (1), the mass ratio of the sugar alcohol phase change material to the organic solvent is 1:(0.8 - 3.2), preferably 1:(1.3 - 2.5).
[0017] Further, in step (1), after collecting the precipitate, water is added, and the mass ratio of the sugar alcohol phase change material to water is 1:(1 - 5), preferably 1:(2 - 3.5).
[0018] Further, in step (1), the organic amine and / or inorganic ammonium is selected from one or more of ammonium chloride, ammonium nitrate, and pentaerythrityl tetramine, preferably pentaerythrityl tetramine.
[0019] Further, in step (1), the mass ratio of the sugar alcohol phase change material to the organic amine and / or inorganic ammonium is 1:(0.1 - 1), preferably 1:(0.3 - 0.6).
[0020] Further, in step (1), dialysis is carried out using a dialysis bag with running deionized water. The cut-off molecular weight of the dialysis bag is 3000 - 15000, preferably 6000 - 11000.
[0021] Further, in step (1), the dialysis time is 12h - 120h, preferably 50h - 80h.
[0022] Further, in step (1), the freeze-drying temperature is -100°C to -10°C, preferably -70°C to -40°C. The freezing time is 8h - 90h, preferably 20h - 45h.
[0023] Further, in step (2), the heating and melting conditions are a temperature of 100°C to 230°C and a time of 3h to 8h. The heating and melting are carried out under closed conditions.
[0024] Further, in step (2), the carrier gas is an inert gas and / or nitrogen, and the inert gas is selected from any one of high-purity nitrogen, high-purity helium, and high-purity argon.
[0025] Further, in step (2), the ratio of the purified sugar alcohol phase change material to the flow rate of the carrier gas is 1g:(0.25 mL / min - 1.15 mL / min), preferably 1g:(0.5 mL / min - 0.75 mL / min), the time is 20min - 40min, and the pressure is 0.8 atm - 1.2 atm.
[0026] Further, in step (2), a carrier gas is introduced to form uniform bubbles inside the sugar alcohol phase change material.
[0027] The second aspect of the present invention provides a sugar alcohol phase change material obtained by the above processing method.
[0028] Further, the phase change temperature point of the sugar alcohol phase change material is 90°C to 180°C, the latent heat of phase change value is 200 J / g to 400 J / g, and the supercooling degree is less than 100°C.
[0029] Further, after 100 consecutive endothermic-exothermic cycles of the sugar alcohol phase change material, the loss rate of its latent heat of phase change value is 0.2% to 1.5%, and the supercooling degree is less than 100°C.
[0030] Further, preferably, the phase change temperature point of the sugar alcohol phase change material is 115°C to 130°C, and the latent heat of phase change value is 280 J / g to 340 J / g.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] (1) The method of the present invention processes the sugar alcohol phase change material, and purifies ordinary sugar alcohols from a state of uneven molecular weight and chemical structure into high-quality sugar alcohols with relatively uniform properties through methods such as dialysis bags with different molecular weights and ammonium compound precipitation. In particular, it effectively promotes the deformation of the isomers of the sugar alcohol phase change material, thereby promoting the rapid completion of the crystallization process of the sugar alcohol phase change material, reducing the supercooling degree of the sugar alcohol phase change material, and improving the stability of its multiple endothermic-exothermic cycle processes.
[0033] (2) The method of the present invention introduces a carrier gas (inert gas or nitrogen) into the purified sugar alcohol phase change material to form uniform bubbles inside the sugar alcohol phase change material, which can increase the nucleation sites for the sugar alcohol phase change material, promote the molten sugar alcohol phase change material to be quickly converted from the vitreous state to the crystalline state, further reduce the supercooling degree of the sugar alcohol phase change material, and retain more enthalpy values at the same time.
[0034] (3) The method of the present invention is simple in operation, good in environmental protection, and is conducive to large-scale popularization and application. Description of the Drawings
[0035] Figure 1 It is the endothermic-exothermic curve of the erythritol phase change material obtained after treatment in Example 1 for 100 consecutive times;
[0036] Figure 2 It is the endothermic-exothermic curve of the erythritol phase change material obtained after treatment in Comparative Example 1 for 100 consecutive times. Detailed Embodiments
[0037] The following further illustrates the purification method and effect of the sugar alcohol phase change material of the present invention through examples. The examples are implemented on the premise of the technical solution of the present invention, and the detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0038] In the experimental methods of the following examples, unless otherwise specified, they are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all purchased from regular biochemical reagent stores.
[0039] In the present invention, a DSC-60Plus differential scanning calorimeter produced by Shimadzu Corporation of Japan is used to analyze the phase change temperature point, latent heat of phase change value, and degree of supercooling of the purified sugar alcohol phase change material.
[0040] Example 1
[0041] Take 100 g of erythritol with a phase change temperature of 120.5 °C. After repeated freezing and thawing three times, add 150 g of deionized water and mix evenly. Stir magnetically at 46 °C and 200 rpm for 3 h. Centrifuge and take the supernatant. Concentrate it under vacuum using a rotary evaporator. The vacuum volume is 15% of the original volume. Add 200 g of benzyl alcohol and let it stand for 16 h. Collect the precipitate, dissolve it in 250 g of deionized water, add 50 g of pentaerythritol tetramine, centrifuge and take the supernatant. Then dialyze it against running deionized water using a dialysis bag with a molecular weight cut-off of 8700 for 68 h. Freeze-dry it at -50 °C for 30 h to obtain purified erythritol. Take 50 g of the purified erythritol and transfer it to a three-necked flask with a sealed rubber stopper. Heat it at 200 °C for 5 h. After all the erythritol has melted, introduce high-purity nitrogen at a rate of 30 mL / min to form uniform bubbles inside the erythritol for 25 min at a pressure of 1 atm to obtain erythritol that can be used to prepare phase change energy storage materials.
[0042] Example 2
[0043] Take 100 g of erythritol with a phase change temperature of 120.5 °C. After repeated freezing and thawing three times, add 100 g of deionized water and mix evenly. Stir magnetically at 46 °C and 200 rpm for 3 h. Centrifuge and take the supernatant. Concentrate it under vacuum using a rotary evaporator. The vacuum volume is 15% of the original volume. Add 130 g of benzyl alcohol and let it stand for 16 h. Collect the precipitate, dissolve it in 200 g of deionized water, add 30 g of pentaerythritol tetramine, centrifuge and take the supernatant. Then dialyze it against running deionized water using a dialysis bag with a molecular weight cut-off of 8700 for 68 h. Freeze-dry it at -50 °C for 30 h to obtain purified erythritol. Take 50 g of the purified erythritol and transfer it to a three-necked flask with a sealed rubber stopper. Heat it at 200 °C for 5 h. After all the erythritol has melted, introduce high-purity nitrogen at a rate of 25 mL / min to form uniform bubbles inside the erythritol for 25 min at a pressure of 1 atm to obtain erythritol that can be used to prepare phase change energy storage materials.
[0044] Example 3
[0045] Same as Example 1, except that the mass of deionized water added to 150 g of deionized water after three cycles of freeze-thawing was increased to 250 g, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0046] Example 4
[0047] Same as Example 1, except that after erythritol was repeatedly freeze-thawed and mixed with deionized water, the water bath treatment temperature was increased to 90 °C, the magnetic stirring speed was increased to 600 rpm, and the stirring time was decreased to 0.5 h, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0048] Example 6
[0049] Same as Example 1, except that acetonitrile was used instead of benzyl alcohol, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0050] Example 7
[0051] Same as Example 1, except that N,N-dimethylacetamide was used instead of benzyl alcohol, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0052] Example 8
[0053] Same as Example 1, except that the mass of 200 g of benzyl alcohol was increased to 300 g, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0054] Example 9
[0055] Same as Example 1, except that ammonium chloride was used instead of pentaerythrityl tetramine, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0056] Example 10
[0057] Same as Example 1, except that 50 g of pentaerythrityl tetramine was added, and the mass of pentaerythrityl tetramine was increased to 100 g, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0058] Example 11
[0059] Same as Example 1, except that high-purity nitrogen gas was introduced at a rate of 30 mL / min, and the high-purity nitrogen gas flow rate was decreased to 12.5 mL / min to form uniform bubbles inside erythritol, and other reaction conditions and material compositions remained unchanged, obtaining erythritol that can be used to prepare phase change energy storage materials.
[0060] Comparative Example 1
[0061] Same as Example 1, except that pentaerythritolamine was omitted, and other reaction conditions and material compositions remained unchanged, to obtain erythritol that can be used to prepare phase change energy storage materials.
[0062] Comparative Example 2
[0063] Same as Example 1, except that the process of flowing deionized water through the dialysis bag for dialysis was omitted, and instead, filtration was carried out using a 5A molecular sieve column with a thickness of 30 cm. Other reaction conditions and material compositions remained unchanged, to obtain erythritol that can be used to prepare phase change energy storage materials.
[0064] Comparative Example 3
[0065] Same as Example 1, except that freeze-drying was changed to electrothermal blast drying, and drying was carried out at 50 °C for 24 h. Other reaction conditions and material compositions remained unchanged, to obtain erythritol that can be used to prepare phase change energy storage materials.
[0066] Comparative Example 4
[0067] Same as Example 1, except that the process of introducing high-purity nitrogen into the purified erythritol was omitted. Other reaction conditions and material compositions remained unchanged, to obtain erythritol that can be used to prepare phase change energy storage materials.
[0068] Comparative Example 5
[0069] According to the method described in CN112815756A, the sugar alcohol was placed in a vacuum tube furnace and heated at 180 °C for 2 h. After the sugar alcohol was completely melted, the THP-24 antioxidant and stearate were added to the molten sugar alcohol, and then magnetic stirring was carried out at 180 °C to uniformly mix the antioxidant and stearate in the sugar alcohol to obtain a sugar alcohol phase change heat storage material. When the sugar alcohol phase change heat storage material in the insulating plastic cavity was in the liquid phase, the working fluid was input from the annular coiled pipe, the external power supply was turned on, and after applying current, the electrodes at the upper and lower ends of the liquid-phase sugar alcohol phase change heat storage material attracted cations and anions respectively. The movement of the cations and anions would drive the flow of the phase change material, enhance the disturbance, and strengthen the heat transfer performance. The working fluid contacted and exchanged heat with the phase change material through the annular coiled pipe to achieve heating or heat preservation.
[0070] Comparative Example 6
[0071] According to the method described in CN112011312A, 25.5 g of erythritol and 4.5 g of disodium succinate hexahydrate were taken and ground evenly. The mixture was slowly heated to 135 °C on a magnetic stirrer. When an appropriate amount of liquid was generated, stirring was started. After all the solids disappeared, insulation was carried out at this temperature for 0.8 h to obtain a colorless transparent liquid. The colorless transparent liquid was naturally cooled to room temperature to obtain a white solid, which was the phase change energy storage material.
[0072] Test Example 1
[0073] The thermal properties of the sugar alcohol phase change materials in Examples 1-11 and Comparative Examples 1-6 were measured, and the specific results are shown in Table 1.
[0074] Table 1 Thermal property data of the sugar alcohol phase change materials measured in the examples and comparative examples
[0075]
[0076] From Table 1, Figure 1 and Figure 2 it can be seen that the samples of the examples of the present invention have good physical and chemical properties and thermal properties. The latent heat of phase change value and supercooling degree of the sample of Example 1 are 329.6 J / g and 73 °C respectively. After 100 consecutive endothermic-exothermic cycles, the loss rate of the latent heat of phase change value and the supercooling degree are 0.2% and 76.5 °C respectively, and the melting phase change temperature points before and after the cycle are relatively close. The latent heat of phase change values of the samples of the comparative examples are generally lower than 270 J / g, and the supercooling degrees are generally greater than 100 °C.
Claims
1. A method for treating a sugar alcohol phase change material, comprising the following steps: (1) After freeze-thawing, the sugar alcohol phase change material is mixed with water, reacted, centrifuged to obtain the supernatant, concentrated, then an organic solvent is added and allowed to stand. After obtaining a precipitate, it is dissolved in water, and then an organic amine and / or an inorganic ammonium is added and mixed. The supernatant is taken, dialyzed against running water, and freeze-dried to obtain a purified sugar alcohol phase change material; (2) The purified sugar alcohol phase change material obtained by freeze-drying in step (1) is heated and melted, and a carrier gas is introduced to obtain a treated sugar alcohol phase change material.
2. The method according to claim 1, wherein, in step (1), the sugar alcohol phase change material is selected from at least one of sugar alcohols with a phase change temperature in the range of 90°C to 180°C.
3. The method according to claim 1, wherein, in step (1), the freeze-thawing is at least three times or more; and / or, in step (1), after the sugar alcohol phase change material is freeze-thawed, water is added, and the mass ratio of the sugar alcohol phase change material to water is 1:(0.6 - 2.5).
4. The method according to claim 1, wherein, in step (1), the reaction is a heating dynamic reaction, the temperature is 35°C to 90°C; the stirring speed is 50 rpm to 600 rpm, and the stirring time is 0.5 h to 8 h.
5. The method according to claim 1, wherein, in step (1), the concentration treatment is under vacuum conditions. After the vacuum concentration treatment, the volume of the vacuum object is 8% to 45% of the original volume.
6. The method according to claim 1, wherein, in step (1), the organic solvent is selected from one or more of acetonitrile, N,N-dimethylacetamide, and benzyl alcohol.
7. The method according to claim 1, wherein, in step (1), the mass ratio of the sugar alcohol phase change material to the organic solvent is 1:(0.8 - 3.2); and / or, in step (1), after collecting the precipitate, water is added to the sugar alcohol phase change material, and the mass ratio of the sugar alcohol phase change material to water is 1:(1 - 5).
8. The method according to claim 1, wherein, in step (1), the organic amine and / or inorganic ammonium is selected from one or more of ammonium chloride, ammonium nitrate, and pentaerythritol tetramine; and / or, in step (1), the mass ratio of the sugar alcohol phase change material to the organic amine and / or inorganic ammonium is 1:(0.1 - 1).
9. The method according to claim 1, wherein, in step (2), the heating and melting conditions are a temperature of 100°C to 230°C and a time of 3 h to 8 h.
10. The method according to claim 1, wherein, in step (2), the carrier gas is an inert gas and / or nitrogen, and the inert gas is selected from any one of high-purity nitrogen, high-purity helium, and high-purity argon.
11. The method according to claim 1, wherein, In step (2), the ratio of the purified sugar alcohol phase change material to the carrier gas flow rate is 1 g : (0.25 mL / min to 1.15 mL / min), the time is 20 min to 40 min, and the pressure is 0.8 atm to 1.2 atm.
12. A sugar alcohol phase change material obtained by the method according to any one of claims 1-11.
13. The sugar alcohol phase change material according to claim 12, characterized in that the phase change temperature point of the sugar alcohol phase change material is 90 °C to 180 °C, the latent heat of phase change value is 200 J / g to 400 J / g, and the degree of supercooling is less than 100 °C.
14. The sugar alcohol phase change material according to claim 12, characterized in that after 100 consecutive endothermic-exothermic cycles of the sugar alcohol phase change material, the loss rate of its latent heat of phase change value is 0.2% to 1.5%, and the degree of supercooling is less than 100 °C.
Citation Information
Patent Citations
Phase change energy storage material and preparation method thereof
CN112011312A
Heat storage phase change heat exchanger and method for promoting crystallization of sugar alcohol phase change material and reducing degree of supercooling
CN112815756A